Relatively Compactness on Some Hyperspaces Associated with Riemannian Manifolds - Morawo, Monsuru A (Darul Yasin Al Sys, 2025)
In this paper, we defined relatively compactness on hyperspaces CL(X) and C(X) of Riemannian metric space and relatively compactness theorem about metric spaces in the Gromov sense. Some classes of Riemannian manifolds as applications were defined.